Interpreting Romantic Themes in Counting Crows' Accidentally in Love - Fitriani, Nur; Hasnirah, Hasnirah; Bakri, Fitriyani (Universitas Sulawesi Barat, 2024)
This research aims to interpret romantic themes in Counting Crows’ Accidentally in Love by revealing the meaning of love in the lyrics of the song. It employs a descriptive qualitative research design to identify and interpret the meaning of the song. The primary data of this research was obtained from Counting Crows’ Accidentally in Love and secondary data from internet webs, journal articles, textbooks, and other online resources. The data was analyzed by using Braun and Clarke’s thematic analysis which consists of six steps: (a) familiarizing with the data; (b) generating initial codes; (c) searching for themes; (d) reviewing themes; (e) defining and naming themes; and (f) producing the report. The data was also interpreted by using Roland Barthes’ semiotic concept: denotation, connotation, and myth. The result of the research reveals that the song describes the author's feeling of being in accidental love when he does not know anything about love before. His feelings and experiences are associated with falling in love unexpectedly, including chaos, happiness, uncertainty, courage, hope, and magic. The meaning of his love in this song is an experience that is unexpected, full of excitement, and sometimes chaotic, but also provides deep meaning and happiness.